Pengaruh NPL dan LDR Terhadap ROA Bank BUMN - Guva Tirta Aji; Dika Puspitaningrum (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
The banking sector, particularly State-Owned Banks (BUMN), is a crucial pillar of financial system stability and a key driver of national economic activity. This dual strategic role requires state-owned banks to maintain profitability (measured by Return on Assets/ROA) while simultaneously controlling inherent risks, particularly credit risk and liquidity risk. The primary objective of this investigation is to empirically evaluate the influence of credit risk, proxying via Non-Performing Loans (NPLs), alongside liquidity risk, characterized by the Loan to Deposit Ratio (LDR), regarding the Return on Asset (ROA) within state-owned banks in Indonesia. The analysis utilizes secondary datasets extracted from the quarterly financial statements of state-owned banks listed on the Indonesia Stock Exchange, procured from authoritative banking disclosures and the Indonesian Banking Statistics released by the Financial Services Authority (OJK). The research approach used is quantitative associative causality through panel data regression analysis, with narrative presentation and interpretation of the results without the use of mathematical formulas. The main outcomes reveal that Non-Performing Loans possess a substantial negative influence on Return on Asset, implying that an escalation in Non-Performing Loans intensifies the burden on bank earnings due to elevated provisioning costs (CKPN). In contrast, the Loan to Deposit Ratio demonstrates a positive yet statistically insignificant influence on Return on Asset. This lack of significance is associated with the state-owned bank's policy of maintaining liquidity at a safe level, which has resulted in increased cost of funds and the operating expenses relative to operating income (BOPO) metric, thereby neutralizing the prospective profit gains resulting from vigorous credit growth. The deductions from this study highlight the necessity of reinforcing more proactive credit risk management and optimizing funding strategies to reduce operating costs and drive sustainable profitability.